Workshop Membangun Pelayan Publik Yang Anti Korupsi - Ridianto, Ridianto; Ilham, Debi Afriansyah; Khofifah , Devia; Munthe, Abdul Kholik; Junius, Wiwin (Jurnal Kewirausahaan dan Bisnis, 2021)
The workshop "Building Anti-Corruption Public Servants" is an event that aims to increase understanding and awareness of the importance of integrity in public services. The event discussed various strategies and best practices in building an organizational culture that upholds ethical and anti-corruption values. Participants were invited to understand the negative impact of corruption on society and the economy, and how each individual in the public service has an important role in preventing it. In addition, the workshop also provided a platform for participants to share experiences and learn from real cases in handling corruption cases in various public service sectors. In this workshop, participants were provided with insights on the role of supervisory and regulatory institutions in overseeing and preventing acts of corruption in the public service environment. Discussions included various legal instruments and policies that have been implemented in an effort to eradicate corruption, as well as strategies to improve transparency and accountability in the management of public funds. In addition, the importance of continuous training and education for public servants to strengthen their capacity to deal with corruption challenges was also a key focus of the workshop.